Inhuman Humanity: On the Theater of Angela Di Maso - Andrea F. De Carlo; Angela Di Maso (Pamiętnik Teatralny, 2023)
This article discusses Angela Di Maso’s theater, which is a reflection on contemporary society and aims to awaken audiences from social conformity and consumerism. This theater seeks to explore human existence, with its metaphysical anxiety, violence, and the brutality of everyday life present. It challenges social norms and stereotypes, using crude language to tell stories that disturb and provoke self-analysis. Angela Di Maso’s theater has gained recognition and success for its versatility in combining textual and scenic elements, meticulously developed with actors. Di Maso’s work combines tradition and innovation, drawing inspiration from European theater and at the same time representing a form of resistance to traditional and avant-garde theatrical conventions, forging new paths of expression and advocating freedom of expression. The article includes as an appendix an extensive interview with Angela Di Maso, entitled “From Jerzy Grotowski to Angela Di Maso, via Witold Gombrowicz: An Interview with an Enfant Terrible of Italian Theater.”